The problem of slavery in the age of emancipation - Davis, David Brion (New York : Vintage, 2014)
"From the revered historian, the long-awaited conclusion of the magi sterial history of slavery and emancipation in Western culture that has been nearly fifty years in the making. David Brion Davis is one of th e foremost historians of the twentieth century, and in this final volum e in his monumental trilogy on slavery in Western culture he offers hig hly original, authoritative, and penetrating insight into what slavery and emancipation meant to Americans. He explores how the Haitian revolu tion respectively terrified and inspired white and black Americans, and offers a surprising analysis of the complex and misunderstood signific ance of colonization-the project to move freed slaves back to Africa-to members of both races and all political persuasions. Davis vividly por trays the dehumanizing impact of slavery, as well as the generally unre cognized importance of freed slaves to abolition. And he explores the i nfluence of religion on American ideas about emancipation. Above all, h e captures the ways in which America wrestled with the knotty problem o f moving forward into an age of emancipation. This is a landmark work: a brilliant conclusion to one of the great works of American history"--
Includes bibliographical references (p.345-403) and index.
Keywords: American colonization society; Slavery -- United States -- History -- 19th century; Slaves -- Emancipation -- United States; Free African Americans -- History -- 19th century; Antislavery movements -- United States -- History -- 19th century; Antislavery movements -- Great Britain -- History -- 19th century; African Americans -- Colonization -- Africa